Sound coaching: tending to the heard in American football films. Issue 1 (2nd January 2016) - Chare, Nicholas
Abstract: This study focuses on how the use of sound, particularly dialogue, in American football films contributes towards the depiction of varied forms of coaching behaviour and practice. Building on a pre-existing investigation that employed Any Given Sunday as a research tool to analyse motivational speeches, the study begins by addressing some of the difficulties that potentially accompany film-based research into sports coaching. It then examines how differing approaches to coaching involving emotional intelligence or the calculated use of performance data are communicated through dialogue such as motivational speeches. The study concludes by attending to the interrelated issues of sexism and zoomorphism in cinematic portrayals of emotion-driven football coaching.